Renoprotective effect of candesartan in patient with diabetes mellitus and hypertension - Sajad Moneim Al-Jubouri; Reem aljanabi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Patients with diabetes and hypertension often have renal function and blood pressure issues, which can increase the risk of cardiovascular events and kidney failure. Angiotensin receptor blockers (ARBs) like candesartan reduce blood pressure and may protect the kidneys. This 8-week study examined how candesartan affected renal function and blood pressure in diabetics and hypertensives. A control group (Group 1) and three diabetes and hypertension groups (Groups 2, 3, and 4) each had 30 participants in this cohort longitudinal study. Group 1 received no medication, whereas Groups 3 and 4 received 16 mg and 8 mg candesartan daily. Group 2 was untreated during the research. During the 8-week study, serum creatinine, GFR, blood pressure, and proteinuria were measured weekly. The findings showed that candesartan improved renal function and blood pressure. Serum creatinine and proteinuria decreased significantly (2.71±0.6 to2.06±0.54), (36.4±3.8 to 23.64±3.52) respectively in Group 3, which received more candesartan. GFR improved significantly (72±9.27 to 83± 6.85) in this group during the research. Group 4 showed statistically significant improvements with a reduced candesartan dose. Group 3 had a greater blood pressure drop than Group 4. All changes were found to be statistically significant, with p-values below 0.05. In conclusion, candesartan improves renal function and lowers blood pressure. In diabetics and hypertensives. The findings suggest that increasing dosage may have greater benefits. This study adds to the evidence that candesartan is useful in treating renal and cardiovascular risk individuals. Additional research is needed to determine the best medicine administration methods and long-term results.